Exploring Brand Loyalty in Online Shopping: The Context of Vietnam's Household Appliances Market - Dong Tan*, Thai (Journal of Economics and Administrative Sciences, 2024)
In the dynamic e-commerce landscape, where online shopping has become a fundamental aspect of consumer behavior, a profound comprehension of the factors influencing brand loyalty is imperative for businesses striving to excel in the digital marketplace.This study aims to investigate the factors influencing brand loyalty of consumers in Viet Nam, with a specific focus on household appliance brands. Additionally, it seeks to elucidate the mediating role of customer satisfaction and brand trust in influencing brand loyalty. The study provides valuable information for developing effective brand strategies, helping strengthen customer loyalty, and increasing market share for home appliance brands. The research will employ a qualitative and quantitative approach, gather primary data through a structured questionnaire survey. The data analysis will be conducted using Smart PLS 4 and SPSS 26. The results of the study indicate that there are several factors influencing brand loyalty, including brand image, brand indentification, brand awareness, brand trust, and customer satisfaction. This underscores the importance of applying the research findings to optimize brand management and marketing strategies.  Paper type Research paper